Finnish pre-service teachers’ identity development after a year of initial teacher education: Adding, transforming, and defending - Varis Sotiria; Heikkilä Mirva; Metsäpelto Riitta-Leena; Mikkilä-Erdmann Mirjamaija (Elsevier Ltd, 2025)
Amidst the broad range of teacher competencies, professional beliefs and professional identity are two important domains of personal orientations that inform teacher quality. This study examines how pre-service teachers have negotiated their professional identity after their first year in initial primary teacher education. The study uses qualitative data from an online survey voluntarily answered by seventy-two Finnish pre-service teachers in Spring 2022. The data were thematically analyzed and further examined for additive, transformative, and defensive identity development using Ruohotie-Lyhty's (2018) framework of teachers' identity-agency. The study supports the notion of identity as social, multiple, and discontinuous.